Diagnostic study of Toxoplasma gondii in students of Thi-Qar university-Iraq by Real- Time PCR - Al-Mosawi, Rabab (University of Thi-Qar Journal of Science, 2015)
Toxoplasma gondii is a unique intracellular parasite, which infect a large proportion of the world, population, butclinically un commonly causes significant disease. The present study was performed for the first time in Thi-Qarprovince to estimate the prevalence of toxoplasmosis among university students . Venous blood samples were collected from 319 (111 males and 208 females) apparently healthy students ,they have ages between (18-42) years attended from different colleges of Thi-Qar university-Iraq, during the period from October 2013 to April 2014. Enzyme linked Immunosorbant Assay (ELISA), was used to evaluate the presence of anti-Toxoplasma IgM and IgG antibodies and detection of B1 gene of T.gondii DNA by Real-Time Polymerase Chain Reaction(RT-PCR). The results indicated that 70 (21.94%) of students were exposed positive for anti-Toxoplasma antibodies,17 (5.33%) of them had IgM,38 (11.91%) had IgG, and 15 (4.70%) had both IgM and IgG. Statistically, significant difference between them. The results showed significant difference between males and females in rate of positive for anti- Toxoplasma antibodies,  which recorded 24 (7.52%) and 46 (14.42%) respectively . Besides the serological diagnosis of T.gondii Real-Time PCR  (RT-PCR) technique was used to confirm the infection with T.gondii by detection B1 gene of T.gondii DNA in the blood of students. out of 319 students only 6.26% showed positive toxoplasmosis among those 8(2.50%)were males  and 12(3.76%) were females. The positive result in RT-PCR analysis were distributed on the patterns of the antiToxoplasma antibodies by ELISA test , it was no found any positive blood samples with IgM,IgG.